Sistem Pengelolaan Zakat dalam Perspektif Hadis Riwayat Bukhari dan Muslim dan Pasal 1, 2, dan 5 UU No. 23 Tahun 2011 - Dea Meisy Wulandari; Tajul Arifin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Zakat is one of the pillars of Islam that must be carried out by Muslims who have met certain requirements. Zakat management is very important so that its distribution is right on target and can realize social justice. In the authentic hadith narrated by Imam Bukhari and Muslim, zakat is managed by amil who is responsible for distributing it to eight groups of recipients. In Indonesia, zakat management is also regulated in Law No. 23 of 2011. Articles 1, 2, and 5 of the law explain the definition of zakat, management principles, and authorized institutions. This article examines the conformity between the principles of zakat management in the hadith and the law, and how the two can support each other for effective zakat management in accordance with sharia.